Inorganic Ba–Sn nanocomposite materials for sulfate sequestration from complex aqueous solutions. Issue 4 (14th March 2018) - Johnson, Isaac E.; Chatterjee, Sayandev; Hall, Gabriel B.; Burton, Sarah D.; Campbell, Emily L.; Conroy, Michele A.; Du, Yingge; Fujimoto, Meghan S.; Varga, Tamas; Kruger, Albert A.; Levitskaia, Tatiana G.
Abstract : Novel functionalBa–Sn nanomaterials for separation or in situ sequestration of sulfate from complex aqueous carbonate solutions were developed. Abstract : Selective sequestration of sulfate (SO4 2− ) in the form of barite (BaSO4 ) from alkaline solutions of high ionic strength containing carbonate is problematic due to the preferential formation of BaCO3 . Incorporation of sulfate into the insoluble and thermally stable BaSO4 phase can potentially benefit radioactive waste processing by reducing operational challenges and suppressing volatilization of other waste components such as technetium-99. To enhance selectivity of SO4 2− sequestration, a series ofBa–Sn nanocomposite materials was prepared using simple hydrothermal synthesis from different Sn(ii ) and Sn(iv ) precursors. Structural characterization indicated that all obtained products predominantly contained BaSn(OH)6 and Ba2 SnO2 (OH)4 ·10H2 O nanocrystalline phases which were disrupted upon exposure to SO4 2− due to formation of BaSO4 . Performance of theBa–Sn materials was tested using complex alkaline solutions simulating radioactive waste containing 0.094 M SO4 2− and 0.5 M CO3 2− among other constituents. About 54–66% of SO4 2− was converted to BaSO4 when a quantity ofBa–Sn material containing approximately a stoichiometric amount of Ba 2+ relative to SO4 2− was used. In comparison, previous studies indicate negligible BaSO4 formation under similar conditions when a simple Ba 2+ salt is used. This improvement is attributed to the selective replacement of the stannate by SO4 2− . Thermal stability of the sulfate-loaded product material up to 1100 °C was demonstrated. The obtained materials promise a convenient and economical option for the selective sequestration or removal of SO4 2− from complex carbonate containing solutions.